Kadar ZINK ASI pada Ibu Postpartum Minggu Pertama - Rini Mustikasari Kurnia Pratama; Diane Marlin (Universitas Baiturrahim, 2021)
One third of the world's people in developing countries are deficient in zinc. The zinc concentration of pregnant women has decreased by up to 20-30% due to increased zinc absorption, especially in the second and third trimesters compared to those who are not pregnant. The research method used is descriptive analytic with cross sectional approach. The research was conducted in the Talang Bakung Community Health Center Jambi City. The sampling technique was purposive sampling in April - August 2020, the samples was 11 postpartum mothers the first week with anemia and 11 postpartum mothers the first week without anemia. Univariate analysis was used for zinc levels in breast milk in first week postpartum women with anemia and no anemia. Research conducted using the Atomic Absorption Spectrometry (AAS) method to see the zinc levels in breast milk (ASI) can prove that there is no significant difference in zinc levels in breast milk in postpartum mothers with anemia and first week postpartum mothers without anemia. Thanks to the Ministry of Research and Technology / National Research and Innovation Agency (Kemenristek / National Agency for Research and Innovation) as a source of funding for research implementation